Evaluation of the different thresholding strategies for quantifying choriocapillaris using optical coherence tomography angiography - Laiginhas, Rita (2020)
Background: In this paper, we evaluate the different thresholding strategies that have been used for the quantification of the choriocapillaris (CC) and explore their repeatability and the interchangeability of the measurements resulting from its application. Methods: Observational study. Eighteen eyes from nine healthy volunteers aged >18 years were imaged four consecutive times with a SD-OCTA system (Heidelberg Engineering, Germany) using a 10°×10° high-resolution protocol centered on the fovea. Projection artifacts were removed, and the CC was bracketed between 10 and 30 µm below Bruch’s membrane. For the quantification of CC, we used four flow deficits (FD) parameters: FD number, mean FD size, total FD area and FD density. We performed a systematic review of literature to collect the thresholding methods that have been used for the quantification of CC. The CC quantification parameters were then evaluated after applying each of the thresholding strategies. Intraclass correlation coefficient (ICC) and Pearson’s correlation analysis were used to compare the repeatability and interchangeability among the different thresholding strategies for quantifying the CC. Results: A total of 72 optical coherence tomography angiography (OCTA) examinations were considered. The systematic review allowed us to conclude that three local thresholding strategies (Phansalkar, mean and Niblack) and three global thresholding strategies (mean, default, Otsu) have been used for CC quantification. These strategies were evaluated in our observational study. We found a high agreement within the same method in the quantification of FD number, mean FD size, total FD area and FD density but a poor agreement with different strategies. Local strategies achieved a significantly superior ICC than global ones in CC quantification. Conclusions: In conclusion, the interchangeability of the CC quantification using different thresholding strategies is low, and direct comparisons should not be performed. Local thresholding strategies are significantly superior to global ones for quantifying CC and should be preferred. There is an unmet need for a uniform strategy to quantify CC in future studies.